Current Legal Issues Affecting Central Banks, Volume III. - Effros, Robert (Washington, D.C. : International Monetary Fund, 1995)
Volume III, edited by Robert C. Effros, contains the collected views of banking and legal experts, gathered at the third IMF-sponsored seminar of central banks general counsels. Matters of both international and domestic concern are addressed. The contributors analyze topics covering developments in international financial institutions; the progress of the European Union toward monetary union and a unified banking and securities market; the economic reform of Latin America; the resolution of the debt crisis; and banking regulations and reform in the United States, the United Kingdom, and Canada.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet